Management Education – The Psychology of the English Language the Importance of Sport, In Learning a Foreign Language - Allegra, Stefania (International Journal of Scientific Research and Management (IJSRM), 2020)
It’s normal and important to understand the role of the applied linguistic in everyday life.It’s an important rule to understand the role of the educational psychology of the foreign language learning.You find many difficult phases in this study according to the age and culture, so the place where you live.To understand the process of the learning about L2, as foreign language, it’s something that needs a special attention in psychology.Psychology is part of the rule that manages the whole life. There are aspects of ourselves that must go together in inner Self life and external life.A professor must have the average knowledge about the psychology of the person. If you don’t apply the teaching with psychology, you can’t have the minimum and the top results in your students.There are awareness concepts in the teaching process, it’s a result of the going on in the ability adaptation of the mind, in memorization techniques.It’s particular to understand that the memorisation techniques are difficult steps to obtain.It depends on the age the ability to learn a language fast; it means it’s an easier process in children; young teenagers are surely trained at school so they can get good results; adults are not so strong in memorization if they are far from studies processes that activate the mind in a properly way training in order to learn a foreign language.In all these processes is very important the practice of sport, because of improvement of mind processes.